2008
DOI: 10.1002/jctb.2010
|View full text |Cite
|
Sign up to set email alerts
|

An optimization study on microwave irradiated decomposition of phenol in the presence of H2O2

Abstract: BACKGROUND: Removal of phenol from industrial waste waters involves basic techniques namely extraction, biodegradation, photocatalytic degradation, etc. Among the available processes, the oxidation of phenols using H 2 O 2 is a suitable alternative because of low cost and high oxidizing power. The application of an oxidation process for the decomposition of stable organic compounds in waste water leads to the total degradation of the compounds rather than transferring from one form to another. Since oxidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
1
11
0
2
Order By: Relevance
“…MW irradiation has successfully been used with H 2 O 2 to produce HO• (Prasannakumar et al 2009). The formation of HO• in MW/H 2 O 2 system occurs similarly to UV/H 2 O 2 , so that the MW irradiation splits the H 2 O 2 molecule into two radicals and so on.…”
Section: Alternatives For Uv Radiationmentioning
confidence: 98%
“…MW irradiation has successfully been used with H 2 O 2 to produce HO• (Prasannakumar et al 2009). The formation of HO• in MW/H 2 O 2 system occurs similarly to UV/H 2 O 2 , so that the MW irradiation splits the H 2 O 2 molecule into two radicals and so on.…”
Section: Alternatives For Uv Radiationmentioning
confidence: 98%
“…In the presence of carbon, the amount removed increased but the heating method and presence of H 2 O 2 had no significant impact. Several studies have reported an increase in the removal of organic compounds by H 2 O 2 under microwave irradiation [10,[26][27][28][29]. As pointed out by Nascimento and Azevedo [30], however, there was no clear evidence whether the observed increase in H 2 O 2 activity was due to non-thermal (e.g., enhanced formation of hydroxyl radicals) or thermal effects of microwave irradiation (e.g., higher heating rate and reaction temperature in the microwave oven compared to conventional heating sources).…”
Section: Removal Of Methyl Orange Under Microwave Irradiation In the mentioning
confidence: 99%
“…Furthermore, as reported in literature [30], microwave was able to promote the generation of hydroxyl radials via H 2 O 2 decomposition, leading to improve the oxidative capacity of system. Comparing with the result obtained form thermostatic heating, the removal efficiency of phenol by microwave was as higher as 20%.…”
Section: Possible Mechanism Of Microwave On Ferric Hydrolysismentioning
confidence: 74%